2016
DOI: 10.5539/elt.v9n12p62
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ and Students’ Attitudes towards L1 Use in EFL Classrooms in the Contexts of Bangladesh and Saudi Arabia

Abstract: <p>The role of a mother tongue (L1) in the teaching and learning of a foreign language (FL) has been the subject of much debate and controversy. This paper reports on a piece of research carried out in our own teaching environments (at universities both in Bangladesh and Saudi Arabia) and presents an analysis of the attitudes of students and teachers towards the use of learners’ mother tongue (in this case Bengali and Arabic) in English language classrooms at the tertiary level where English is taught as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…In line with these researches, Lo [2] found that insight shifting of the role play in learning foreign languages beginning to show its effect on the classrooms practice. Shuchi & Islam [25] propose that "a judicious and moderate use of L1 does not hinder learning; rather, it assists, aids and facilitates the teaching and learning process thus providing the teacher with an effective pedagogical tool for maximizing the learning outcomes".…”
Section: Introductionmentioning
confidence: 99%
“…In line with these researches, Lo [2] found that insight shifting of the role play in learning foreign languages beginning to show its effect on the classrooms practice. Shuchi & Islam [25] propose that "a judicious and moderate use of L1 does not hinder learning; rather, it assists, aids and facilitates the teaching and learning process thus providing the teacher with an effective pedagogical tool for maximizing the learning outcomes".…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, students can use E-learning resources to acquire the four main English language skills (listening, speaking, reading, and writing) (Yang & Chen, 2007;Shuchi, & Islam, 2016). This section elaborates on the affordances of E-learning today, and discusses the implications for Saudi students, while also identifying the challenges associated with these aspects when balancing the argument.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other researchers go further, arguing that the use of the L1 is likely to be an indicator of inadequate proficiency among non-native speaker teachers (Harbord 1992, Turnbull 2001). Thus, the over-use of the L1 may cause confusion and negative consequences for On the basis of the above review, many studies have examined the use and role L1 in the L2 classroom (Ahmad and Jusoff 2009, Carless 2007, De la Campa and Nassaji 2009, Malik 2010, Mansor 2017, Shuchi and Islam 2016, Yavuz 2012. A research study conducted by Shuchi and Islam (2016) in two different teaching contexts (Bangladesh and Saudi Arabia) investigated the use of L1 (Bengali and Arabic) in two universities.…”
Section: The Use Of the L1 (Arabic) In The Classroom And Translationmentioning
confidence: 99%